Occupational Eye Injuries in the agricultural settings: a retrospective study from North-Eastern Italy - Riccò, Matteo; Vezzosi, Luigi; Mezzoiuso, Angelo Giosuè (Acta Biomedica Atenei Parmensis, 2020)
Background: Occupational Eye Injury (OEI) represents a common world-wide event accounting for between 3.3% and 6.1% of all occupational compensation claims. In this retrospective study we evaluated all the recorded OEI which occurred in the Autonomous Province of Trento (APT) during the period 2000-2013. Methods: Data on OEI for all of APT were retrieved an institutional archive and the analysis included demographics of the injured, as well as characteristics and settings of the OEI. In order to assess the risk of OEI in Agricultural Workers (AWs) vs. all other Occupational groups, a multivariate analysis was eventually performed through a logistic regression analysis. Results: A total of 141,139 work-related injuries were recorded, including 5,065 (3.6%) OEI. 91.9% of all cases occurred in males, of Italian origin (77.2%), with a mean age of 38.4±11.7 years. The industrial sector reported the higher share of OEI (70.7%), whereas higher incidence rates were reported among AWs (6.04 vs. 3.85/1,000 workers/year). Agricultural OEI occurred in older workers (45.6±13.3 vs. 37.1±11.0 years), being more likely associated with “contusions” (OR 2.042, 95% 1.602-2.602) and “lacerations” (OR 2.386, 95%CI 1.877-3.033), and less frequently with exposures to chemicals, gases and vapours (OR 0.478, 95%CI 0.279-0.817). Conclusions: Despite a relatively low frequency of OEI, AWs were affected with a seemly higher incidence than that reported in other occupational groups. OEI in AWs exhibited a specific pattern, both in terms of lesion, and settings of the events, recommending tailored interventions in order to improve promotion strategies. (www.actabiomedica.it)